Entrepreneurship in the Shadow Economy: A Review of the Alternative Policy Approaches - Collin C Williams (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2015)
The aim of this paper is to review the various policy approaches that can be used to tackle entrepreneurship in the shadow economy. To do this, it firstly reviews four possible policy options, namely taking no action, eradicating shadow entrepreneurship, moving legitimate entrepreneurship into the shadow economy, or transforming shadow entrepreneurship into legitimate entrepreneurship. Revealing that transforming shadow entrepreneurship into legitimate entrepreneurship is not only the most viable option but also the approach most commonly adopted by supra-national agencies and national governments, a review is then undertaken of how this can be achieved using either direct controls, which seek to increase the costs of shadow entrepreneurship and/or the benefits of legitimate entrepreneurship, or indirect controls that seek to generate a commitment to compliance and greater self-regulation. How these approaches can be combined is then reviewed. The outcome is a comprehensive review and evaluation of the various policy approaches available to policy-makers for addressing shadow entrepreneurship along with some recommendations regarding the way forward.